PELAKSANAAN WORKSHOP DAN BIMBINGAN BERKELANJUTAN UNTUK MENINGKATKAN KOMPETENSI GURU DALAM MENYUSUN RENCANA PELAKSANAAN PEMBELAJARAN (RPP) - Nurzali Nurzali (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
This study aims to determine the improvement of teacher competencies in preparing plans for implementing learning in 008 Sungai Primary School, Sigajah and 013 Public Elementary School, Teluk Piyai, through continuous workshops and guidance. The subjects of this study were 008 State Elementary School teachers, Sigajah River, and SDN 013 Piyai Bay, totaling 24 teachers. This study uses school action research with two cycles. The technique of collecting data uses an observation sheet on the preparation of plans for implementing learning carried out by the teacher. The school action research is carried out in the odd semester of the 2018/2019 academic year for approximately two months, from September to November 2018. The results of the study are 1) workshops and ongoing guidance can increase teacher motivation and competence in preparing a complete learning implementation plan according to the components. The teacher shows the seriousness in understanding and compiling the plan for implementing the learning after getting guidance on the preparation of the learning implementation plan from the researchers in the implementation of the workshop. 2) Continuous guidance can improve teacher competency in preparing learning implementation plans. It can be proven from the results of observations that show that there is an increase in teacher competence in preparing the implementation of learning plans.